On Certain Models of Non-Laminar Flows with Turbulent Diffusion - Burnat, M. (Engineering Transactions, 1985)
A new model of turbulent flow is proposed in the paper; the model takes into account the situation when the mass transport proceeds along two mutually intersecting curvilinear cones. Laminar flow represents the particular case of the model when the cones are reduced to curves.